Stress Induced Lipids Accumulation in Naviculoid Marine Diatoms for Bioenergy Application - Thajuddin, Nooruddin; Ilavarasi, Asokaraja; Baldev, Edachery; MubarakAli, Davoodbasha; Alharbi, Naiyf S.; Chinnathambi, Arunachalam; Alharbi, Sulaiman Ali (International Journal of Biotechnology for Wellness Industries, 2015)
Microalgae are expected to play promising role in the production of biofuel in current research. Two of marine diatoms, Navicula sp. and Amphora sp. were isolated and their growth rate was also studied. Total lipid content was analyzed in stationary growth state under normal conditions. By the two stage process, both the diatoms were subjected to nitrogen and silicon undersupplied for five days and the total lipid accumulation in the diatoms were found to be increased during nutrient deficiency period. The nutrient deficit conditions prone to increased total lipid content and also altered the fatty acid profile in diatom. The total lipid content of Navicula sp. and Amphora sp. were found to be 34.93% DCW and 41.10% DCW under normal conditions and in nitrogen deficiency conditions it has been increased to 60.71% DCW and 64.72% DCW respectively. The major fatty acids were found to be cis-10-Heptadecanoic acid (27.54%) and stearic acid (24.57%). The level of saturated and monounsaturated fatty acids were found to be high in both the diatoms. The presence of low level of polyunsaturated fatty acids indicated that these two organisms could find future application in bioenergy production.